Analisis Nilai-Nilai Moral yang Terkandung dalam Novel “Orang Aneh” Karya Albert Camus dan Relevansinya dalam Kehidupan Sehari-Hari - Analisa Dawolo; Mastawati Ndruru; Lestari Waruwu (Indo-MathEdu Intellectuals Journal, 2023)
Literary work is a place and a place for an author to express a picture of life in which there are creations and imagination as well as support for life experiences that are poured out. Literary works are created to convey moral messages that have deep meaning and cannot be separated from the problems of everyday life. In this study, the main problem is how the moral values ​​in the novel "Orang Aneh" by Albert Camus. This study aims to describe the moral values ​​contained in the novel "Orang Aneh" by Albert Camus. The method used in this research is a qualitative approach with a descriptive research type. techniques in analyzing the data in this study, namely: data reduction, data presentation, and conclusions/verification. Based on the research results, it can be concluded that the moral values ​​contained in the novel "Orang Aneh" by Albert Camus consist of 3 (three) forms of moral values, namely: the moral values ​​of human relations with oneself, the moral values ​​of human relations with other humans, and moral value of human relationship with God